Implementasi Akuntabilitas Kinerja dan Strategi Manajerial dalam Peningkatan Mutu Layanan Pendidikan Formal - Bahar, Alfiana; Hasbullah; Arisal (Jurusan Tarbiyah STAI Al-Gazali Bone, 2024)
The quality of formal education services is the main indicator of the success of educational institutions in carrying out their strategic functions. This study aims to analyze the implementation of performance accountability and managerial strategies in improving the quality of formal education services. This study uses a literature approach by examining a number of scientific articles related to the topic in question. The results of the study show that performance accountability plays an important role in creating transparency and improving the achievement of educational institutions. Managerial strategies, including planning, organizing, implementing, and evaluating functions, have proven to be effective in supporting service quality. In addition, the role of the principal, the pedagogic competence of teachers, the implementation of innovative learning models, and proper classroom management are determining factors in improving quality. These findings imply that the integration of accountability and a systematic and sustainable managerial strategy is key in creating quality formal education.